FEATURES OF ANDROGENESIS IN ANTHER CULTURES OF VARIETIES AND A PROMISING ACCESSION OF SPRING COMMON WHEAT BRED IN WEST SIBERIA DIFFERING IN THE PRESENCE OR ABSENCE OF WHEAT-ALIEN TRANSLOCATIONS - L. A. Pershina; T. S. Osadchaya; E. D. Badaeva; I. A. Belan; L. P. Rosseeva (Вавиловский журнал генетики и селекции)
Androgenesis has been studied in anther cultures of eight cultivars and one promising accession of spring common wheat raised in West Siberia (Siberian Research Institute of Agriculture, Omsk, Russia). The varieties are close in origin but vary in the presence or absence of wheat-alien translocations (wheat–rye 1RS.1BL and wheat–couch grass 7DL-7Ai). The promising accession L-311/00-22 bears the 1RS.1BL translocation and the cytoplasm of cultivated barley Hordeum vulgare L. The main task of the study is to assess the possibility of obtaining dihaploid lines in the genotypes examined bearing wheat-alien translocations. It has been found that different accessions respond differently to anther culture conditions depending on the concentration of 2,4-D in the initial medium. Accession L-311/00-22 is best for androgenesis experiments and raise of dihaploid lines. The dependence of the effect of the genotypic environment of wheat on the effect of wheat-alien translocation on androgenesis features, is discussed.